Implementation of Tajribi, Burhani, Bayani, and 'Irfani Methods in Islamic Education Philosophy - Yuri Indri Yani; Salminawati Salminawati; Usiono Usiono (Academia Open, 2025)
General Background: Epistemology, as a core branch of philosophy, critically examines the nature, sources, and limits of knowledge. Specific Background: Within the Islamic intellectual tradition, epistemology encompasses distinct methodologies—tajribi, burhani, bayani, and ‘irfani—each rooted in different epistemic frameworks. Knowledge Gap: However, comprehensive analyses of how these methods are implemented within the context of Islamic education philosophy remain limited. Aims: This study aims to explore the application of Islamic epistemological methods in the study of Islamic educational philosophy. Results: Through qualitative descriptive library research, the study finds that the tajribi (empirical) method is utilized to understand physical realities, the burhani (rational) method to grasp metaphysical concepts, the bayani (textual-interpretative) method to extract meaning from sacred texts, and the ‘irfani (intuitive-spiritual) method to attain inner truths through spiritual practice. Novelty: The study synthesizes these diverse epistemological approaches and delineates their respective educational domains, offering an integrated framework for understanding Islamic knowledge acquisition. Implications: These findings contribute to the broader discourse on Islamic education by highlighting the multidimensional nature of knowledge in Islamic thought and advocating for a balanced pedagogical model that accommodates empirical, rational, textual, and spiritual dimensions. Highlights: Distinct epistemological methods reflect diverse paths to knowledge in Islam. Each method aligns with specific objects: material, rational, textual, or spiritual. Integration of these methods enriches Islamic educational philosophy. Keywords: Islamic Epistemology, Tajribi, Burhani, Bayani, ‘Irfani